Bariery wprowadzania zarządzania wiedzą w przedsiębiorstwie - Smok, Barbara; Nycz, Małgorzata (Barriers of the Knowledge Management Implementations in Enterprise, 2005)
The paper presents the knowledge management implementation problems. At the beginning the idea information society is described, then intellectual capital and its types are presented. The next section covers knowledge management presentation. The following one presents the knowledge management system. Then barriers of the knowledge management implementation are discussed. The final section contains a brief summary.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 240-247